Creating sacred experience for Xi Qinglin Temple of Guilin / Huang Zheng and Eakachat Joneurairatana - Huang, Zheng; Joneurairatana, Eakachat (Universiti Teknologi MARA, 2020)
When Chinese think of Buddhist temple landscape, the image of Chinese Buddhist style in the mainland that is as cultural identity occurs to their perception. But one thing that has been forgotten is the China of Multicultural that has been evolved through the Confucianism, Buddhism and Taoism of improvement, they have impacted each other in the various aspects of cultural integration. As a result, the development of the Chinese Buddhist Temple landscape can only be done by some "routine design style" into the present Chinese Buddhist temple form, which turns to be a Weak identity of the temple landscape. Chinese Buddhist identity is different from other countries. That has been evolved through an improved process. Chinese have seen hidden meaning as a pearl of intangible wisdom under cultural aesthetics. Due to this meaning, The connection between the Chinese Buddhist temple architecture and the landscape is interrupted, which is Chinese have seen "Buddhist Temple aesthetic" that has been" Lost identities" is considered by researchers. This research is intended to creating a designed way of Buddhist temple landscape in china for the sacred experience. The "meanings" and "experience" of landscape, by "Clarified" the Zen Buddhism and Pure Land Buddhism of the Chinese wisdom in connection with the local cultural context, which will Strengthen the identities of Buddhist temples of Local and this may be a significant implication that the Xi Qinglin temple to rebuilding and Promotion of Buddhist Culture.